Pengaruh Disiplin Kerja Dan Komunikasi Terhadap Kepuasan Kerja Pegawai Dinas Perhubungan Kabupaten Tasikmalaya - Fannysa Armalia Triyana; Suci Putri Lestari; Arga Sutrisna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine and analyze the influence of work discipline and communication at the Tasikmalaya Regency Transportation Service Office and its influence on job satisfaction, both simultaneously and partially. This research model uses a survey method. The data collection technique was carried out by distributing questionnaires to 83 permanent employees of the Tasikmalaya Regency Transportation Service Office staff. The data analysis technique uses Multiple Linear Regression Analysis. Based on the research results, it is known that Work Discipline and Communication simultaneously and partially influence Job Satisfaction. Work Discipline and Communication both have a significant effect on Job Satisfaction. Therefore, it is recommended that companies can improve Work Discipline, Communication and Job Satisfaction so that they can have a positive impact and achieve company goals in the future.